c y Douglas Wood ; illustrated by Greg Couch. - Wood, Douglas, 1951- (New York : Simon & Schuster for Young Readers, 1996)
When the fearsome Windigo begins to prey upon the People of the North Woods, a girl named Morning Star comes up with a plan to stop him.
Keywords: Ojibwa Indians -- Folklore; Folklore -- North America